Relationship between central corneal thickness and severity of open angle glaucoma using optical coherence tomography. - Mushawiahti, M; Syed Zulkifli, SZ; Aida Zairani, MZ; Faridah, H (Penerbit UKM, 2011)
Central corneal thickness plays a major role in the management of many types of glaucoma. Therefore, our aim is to determine the relationship between the severity of glaucoma measured by optical coherence tomography (OCT) and central corneal thickness (CCT) among normal tension and high tension glaucoma patients. This is an observational cross sectional study on 190 patients carried out in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Three groups of patients were identified; 60 normal tension glaucoma (NTG), 61 primary open angle glaucoma (POAG) and 69 control. Patients were identified based on the glaucomatous visual field changes and previous record of intraocular pressure before treatment. Visual acuity and intraocular pressure measurements were recorded. Specular microscope was used to measure the CCT and the severity of glaucoma was evaluated objectively based on the retinal nerve fibre layer (RNFL) thickness using optical coherence tomography. Results showed NTG patients had significantly thinner cornea, 503.07±32.27μm compared to the control group, 517.45±31.74 μm (p=0.012). However, there was no significant difference between the CCT of POAG and NTG groups (p=0.386).Retinal nerve fibre layer (RNFL) thickness was significantly different between the glaucoma and the control groups (p<0.05 in all quadrant). However, correlation between CCT and severity of RNFL thinning was only found for the POAG group but not for the NTG group. (mean RNFL and superior quadrant RNFL; r=0.251,0.401) . This study demonstrated the correlation between CCT and severity of glaucoma in POAG patients but not for the NTG group. Therefore, CCT is related to the severity of POAG-related visual loss.